Reflection of the Cyrillo-Methodian Tradition in the Contemporary Macedonian Literature - Stojmenska-Elzeser, Sonja (Slovenský komitét slavistov, Slavistický ústav Jána Stanislava SAV, v. v. i., 2024)
The paper is a brief overview of the literary works in Macedonian contemporary literature devoted to the great importance of Cyril and Methodius Brothers for the culture of all Slavic peoples, and especially for the Macedonian culture. Various literary works from different genres (poetry, prose and drama) from the second half of XX century till now, which refer to the Cyrillo-Methodian tradition are commented. In the paper, their symbolic meanings, motifs and models of literary interpretation are being discussed, such as: admiration and glorification, nationalism, patriotism, Slavdom as unity, details from the Vitae, the glagolica and the diversity within the Slavic world, the motif of the Slovak town of Nitrа, ethical and spiritual questions, the phenomenon of translation, etc. Also, the paper includes some observations on the work of great educators regarding the contemporary challenges of the modern humanity.
Keywords: Cyrillo-Methodian tradition, contemporary Macedonian literature, Slavdom, glagolica, phenomena of translation, cultural icons